A load-dependent PWA-H∞ controller for semi-active suspensions to exploit the performance of MR dampers. (15th July 2019) - Wu, Jian; Zhou, Hongliang; Liu, Zhiyuan; Gu, Mingqin
Highlights: The controller can handle actuator capability, load variation, and road disturbance. A piecewise suspension model and a PQLF-based design method are employed. The controller can exert different damping properties for different load conditions. Abstract: Magnetorheological (MR) dampers enable wide-range adjustment of damping and are considered as promising actuators for suspension performance optimization. However, MR dampers also exhibit complex nonlinearities, including hysteresis and bi-viscosity. Moreover, in addition to handling road irregularities, the suspension system needs to adjust its performance according to variations in vehicle load. The above nonlinearities and requirements both bring challenges to the design of semi-active suspension controllers. In this paper, the nonlinearities of MR dampers are handled with a piecewise modeling method, and the vibration attenuation is realized by designing a static piecewise-affine (PWA) H ∞ controller. Furthermore, to deal with the time-varying load and to fully utilize the capability of MR dampers, a parameter-dependent piecewise-quadratic Lyapunov function (PDPQLF) is employed, which results in a load-dependent PWA (LDPWA) H ∞ controller. Simulation and experimental results under random, bumpy and sinusoidal excitations show that the proposed controller can achieve enhancements on both comfort and handling performance. Above all, the proposed method enables effective high-frequency vibration suppression for underload conditions, while for overload conditions, the low-frequency performance is more significantly improved.